Clavatispora thailandica gen. et sp. nov., a novel taxon of Venturiales (Dothideomycetes) from Thailand - Boonmee, Saranyaphat; Bhat, Jayarama D.; Maharachchikumbura, Sajeewa S.n.; Hyde, Kevin D. (Phytotaxa, 2014)
An unusual wood-inhabiting fungus was found in northern Thailand. The combination of characters of this taxon, viz. setose, ostiolate ascomata, bitunicate asci, dark brown, wedge-shaped to clavate, muriform ascospores, and a hyphomycetous asexual state producing ellipsoidal, septate, highly constricted, holoblastic conidia is not found in any hitherto described genus of Dothideomycetes. An LSU phylogeny showed this taxon to be clearly placed in the family Sympoventuriaceae, Venturiales. The name Clavatispora thailandica gen. and sp. nov., is introduced to accommodate this taxon, which is described and illustrated and compared with other genera in this family.